First trimester versus second trimester down's syndrome screening in the west of Scotland. (18th April 2012) - Wu, P; Villiers, M; McBride, L; Cameron, AD
Abstract : During 2010, we compared performance of first versus second trimester Down's syndrome screening in 2 hospitals 4 miles apart, serving the same population in West of Scotland. As the same regional genetics laboratory is used by both hospitals, confounding factors are avoided. In hospital 1, 2728 patients were screened in first trimester using NT measurement, HCG and PAPP-A. Ninety-three patients were screen positive and the 3 actual cases of Down's syndrome were from this group. Therefore, there is 100% sensitivity, 97% specificity, 3.4% false positive and 3.4% screen positive rates. The screening programme in hospital 2 utilised quadruple markers (AFP, HCG, Inhibin A and unconjugated oestriol) in second trimester. Overall, 3803 patients were screened and 195 patients were deemed high risk. There were 11 actual cases of trisomy 21, 8 were screen positive and 3 screen negative. This gives 73% sensitivity, 95% specificity, 5.1% false positive and 5.1% screen positive rates. As this is a small retrospective audit with few cases of Down's syndrome, it is difficult to accurately compare first and second trimester screening. Literature suggests 92% and 80-85% sensitivity for first trimester and quadruple testing, respectively. Our results show that first trimester screening has a significantly better detection rate than second trimester screening. Although first trimester screening is recommended by National Pregnancy Screening Programme, its implementation has been hampered by lack of sonographers trained in NT assessment. Furthermore, quality control is more difficult in first than in second trimester as sonographer variations are more common than laboratory inconsistencies.